The Development Strategy of Ngusaba Gumang Ceremony As Leading Cultural Tourism Attraction in Golong Village, Narmada District West Lombok Regency, West Nusa Tenggara. - Widiantara, I Gusti Agung Bagus; Suwitra Wirya, I Made; Wartana, I Made Hedy (Jurnal Manajemen Pelayanan Hotel, 2022)
Cultural Tourism Attractions are spread throughout Indonesia, including on the island of Lombok. These tourist attractions contain religious and cultural values which are reflected in the activities of the local community. We must preserve these religious and cultural values in the midst of globalization. Balinese culture, which breathes Hinduism, which has become a tourist attraction, has also been carried over to West Nusa Tenggara Province, especially on the island of Lombok, since ancient times. This form of culture, in the form of the Ngusaba Gumang Ceremony, is considered necessary to be preserved for the sake of realizing sustainable tourism. The location of the ceremony is located in Golong Village, which is quite close to the tourist destinations of Narmada Park, Suranadi Temple, and the famous Golong Golf Course in West Nusa Tenggara but not yet known to tourists. Based on the stages of development, the Ngusaba Gumang ceremony as a cultural tourism attraction is at the Exploration stage. This stage is characterized by limited and sporadic visits from adventurous people. There was intensivecontact with local residents and using facilities owned by residents with very little social and economic impact. Data analysis techniques used in this study include: Qualitative Descriptive Methods and SWOT analysis. From the results of the SWOT analysis above, it can be concluded that the Ngusaba Gumang Ceremony has the potential to continue to be developed as a leading cultural tourist attraction in West Lombok Regency with advantages in cultural and historical tourist attractions with the existence of this ceremony which is associated with various other tourism activities. As for other activities that can be associated with the Ngusaba Gumang Ceremony, such as culinary tours and spiritual tours and locations for tents/traditional markets in Golong Village. Keywords: Ngusaba Gumang Ceremony, Development Strategy, SWOT Analysis